PENGARUH MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR IPA SISWA PADA TEMA 5 SUBTEMA KOMPONEN EKOSISTEM PADA SISWA KELAS V SD NEGERI 016402 MANDOGE - Erika Rahmawati Saragih; Sukardo Sitohang; Yanti Arasi Sidabutar (JOURNAL SAINS STUDENT RESEARCH, 2024)
This resea.rch a.ims to determine the influ.ence of a.u.dio-visu.a.l media. on stu.dents' science lea.rning ou.tcomes in theme V, su.b-theme 1, ecosystem components in cla.ss V stu.dents a.t SD Negeri 016402 Ma.ndoge. There a.re 2 hypotheses in this resea.rch, na.mely: (Ha.) there is a.n influ.ence of a.u.dio-visu.a.l media. on stu.dents' science lea.rning ou.tcomes in theme V, su.b-theme 1, ecosystem components in cla.ss V stu.dents a.t SD Negeri 016402 Ma.ndoge. (Ho) There is no influ.ence of a.u.dio visu.a.l media. on stu.dents' science lea.rning ou.tcomes in theme V, su.btheme 1, ecosystem components in cla.ss V stu.dents a.t SD Negeri 016402 Ma.ndoge. This resea.rch wa.s ca.rried ou.t in the 2023/2024 a.ca.demic yea.r in Ma.y. This resea.rch method is a.n experiment with a. pre-experimenta.l design resea.rch type with a. One-Grou.p Pretest-Posttest Design resea.rch design. This resea.rch sa.mple consisted of 23 stu.dents. The da.ta. collection techniqu.es u.sed a.re tests a.nd docu.menta.tion. Da.ta. were processed u.sing sta.tistica.l a.na.lysis techniqu.es, the N-Ga.jin test a.nd the t test. Ba.sed on the N-Ga.jin test with a. significa.nce of 0.74 > 0.75, it ca.n be conclu.ded tha.t its effectiveness is su.fficient a.nd the hypothesis test obta.ined a. significa.nce of 0.00 < 0.5. It ca.n be conclu.ded tha.t there is a.n influ.ence of va.ria.ble X on va.ria.ble Y. From these resu.lts, it ca.n be seen tha.t Ha. is a.ccepted, which mea.ns tha.t there is a.n influ.ence of a.u.dio-visu.a.l media. on stu.dents' science lea.rning ou.tcomes in theme V, su.b-theme 1, ecosystem components in cla.ss V stu.dents a.t SD Negeri 016402 Ma.ndoge